Perancangan Aplikasi Resep Makanan Pencegah Stunting Menggunakan Metode Design Sprint - francisca, khollydayyana mitra; Kusuma, Wahyu Teja; Khudori, Ahsanun Naseh (Jurnal Informatika dan Komputer, 2025)
Stunting is a health problem that is still a serious concern in Indonesia because of its impact on child growth. One of the main factors causing it is the lack of nutritional education for mothers and parents. To help overcome this, this study designed a food recipe application to prevent stunting using the design sprint method combined with persona, crazy 8's, and MVP (Minimum Viable Product). This combination of methods was chosen because it allows the application design process to be carried out quickly, and based on user needs. The design of this application aims to provide information about healthy food menus that are in accordance with children's nutritional needs, especially in preventing stunting. The design of the application user interface (prototype) was developed based on mobile using figma as a design tool. The application design was evaluated using the SUS method with a result of 77 which means that this application has a good level of usability with the Adjective Rating "GOOD" included in the grade C category. The results of this study indicate that this application has the potential to help parents, pregnant women in choosing and serving healthier and more nutritious food for children. With this application, it is hoped that the stunting rate in Indonesia can be reduced through easier and more practical access to nutritional information.